2001
DOI: 10.1086/322394
|View full text |Cite
|
Sign up to set email alerts
|

Hard Radio Spectra from Reconnection Regions in Galactic Nuclei

Abstract: Extremely flat and inverted radio spectra as observed in galactic nuclei and BL Lac sources are still a challenge for fast particle acceleration models. Continuous acceleration by electric fields in reconnection regions can result in almost constant particle distributions and thereby in inverted synchrotron spectra independent from the details of the injected spectrum. These spectra are calculated from a spatially averaged diffusion transport equation in momentum space that includes systematic momentum gains a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…Relativistic reconnection in ion-electron plasmas has been studied less. We find a test-particle simulation (Romanova & Lovelace 1992), a resolution of the diffusion equation (Birk et al 2001), and a discussion by Sakai et al (2002) in a 2D PIC simulation of laser fusion beams.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Relativistic reconnection in ion-electron plasmas has been studied less. We find a test-particle simulation (Romanova & Lovelace 1992), a resolution of the diffusion equation (Birk et al 2001), and a discussion by Sakai et al (2002) in a 2D PIC simulation of laser fusion beams.…”
Section: Introductionmentioning
confidence: 82%
“…Such attributes made it attractive for high-energy astrophysics to explain, for example, radiation (Romanova & Lovelace 1992) and flares (Giannios et al 2009) in active galactic nuclei (AGNs) jets or in gamma-ray bursts (Lyutikov 2006a;Lazar et al 2009), the heating of AGN and microquasar coronae and associated flares (Di Matteo 1998;Merloni & Fabian 2001;Goodman & Uzdensky 2008;Reis & Miller 2013), the flat radio spectra from galactic nuclei and AGNs (Birk et al 2001), the heating of the lobes of giant radio galaxies (Kronberg et al 2004), the σ-paradox and particle acceleration at pulsar wind termination shocks (Kirk & Skjaeraasen 2003;Pétri & Lyubarsky 2007;Sironi & Spitkovsky 2011), GeV flares from the Crab nebula (Cerutti et al 2012a(Cerutti et al ,b, 2013, transient outflow production in microquasars and quasars (de Gouveia dal Pino & Lazarian 2005;de Gouveia Dal Pino et al 2010;Kowal et al 2011;Dexter et al 2014), gamma-ray burst outflows and non-thermal emissions (Drenkhahn & Spruit 2002;McKinney & Uzdensky 2012), X-ray flashes (Drenkhahn & Spruit 2002), soft gamma-ray repeaters (Lyutikov 2006b;Uzdensky 2011), flares in double pulsar systems (Lyutikov & Lazarian 2013), or energy extraction in the ergosphere of black holes (Koide & Arai 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It is a candidate for explaining (i) particle acceleration at pulsar wind termination shocks (Kirk & Skjaeraasen 2003;Pétri & Lyubarsky 2007;Sironi & Spitkovsky 2011a); (ii) the flat radio spectra from galactic nuclei and AGNs (Birk et al 2001) and from extragalactic jets (Romanova & Lovelace 1992); (iii) GeV flares from the Crab nebula (Bednarek & Idec 2011;Uzdensky et al 2011;Cerutti et al 2012aCerutti et al ,b, 2013; (iv) flares in active galactic nuclei (AGN) jets (Giannios et al 2009) or in gamma-ray bursts (Lyutikov 2006a;Lazar et al 2009); (v) the heating of AGN and microquasar coronae and the observed flares (Di Matteo 1998;Merloni & Fabian 2001;Goodman & Uzdensky 2008;Reis & Miller 2013;Romero et al 2014;Zdziarski et al 2014); (vi) the heating of the lobes of giant radio galaxies (Kronberg et al 2004); (vii) transient outflow production in microquasars and quasars (de Gouveia dal Pino & Lazarian 2005;de Gouveia Dal Pino et al 2010;Kowal et al 2011;Dexter et al 2014); (viii) gamma-ray burst outflows and non-thermal emissions (Drenkhahn & Spruit 2002;Giannios & Spruit 2007;McKinney & Uzdensky 2012); (ix) X-ray flashes (Drenkhahn & Spruit 2002); or (x) soft gamma-ray repeaters (Lyutikov 2006b;Uzdensky 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic reconnection has been invoked as an explanation of the rapid variability observed in active galactic nuclei (Di Matteo 1998). Particle acceleration in the reconnection process has been proposed as operating in radio jets (Romanova & Lovelace 1992;Birk et al 2001).…”
Section: Introductionmentioning
confidence: 99%